2006
DOI: 10.1186/1479-5868-3-23
|View full text |Cite
|
Sign up to set email alerts
|

Moms in motion: a group-mediated cognitive-behavioral physical activity intervention

Abstract: Background: When examining the prevalence of physical inactivity by gender and age, women over the age of 25 are at an increased risk for sedentary behavior. Childbearing and motherhood have been explored as one possible explanation for this increased risk. Post natal exercise studies to date demonstrate promising physical and psychological outcomes, however few physical activity interventions have been theory-driven and tailored to post natal exercise initiates. The purpose of this study was to compare the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 23 publications
(31 reference statements)
5
98
1
Order By: Relevance
“…Albright et al 45 and Fahrenwald et al 46 carried out the physical activity intervention among mothers for 8-weeks and reported an increased level of PA post the intervention. Cramp and Brawley 47 and Miller et al 48 alongside with encouraging PA, they included ways of overcoming barriers to promote PA in the intervention. They demonstrated that the groups, who received exercise treatment in addition to the behavioral intervention, had higher PAL following the intervention.…”
Section: Physical Activity Interventionsmentioning
confidence: 99%
“…Albright et al 45 and Fahrenwald et al 46 carried out the physical activity intervention among mothers for 8-weeks and reported an increased level of PA post the intervention. Cramp and Brawley 47 and Miller et al 48 alongside with encouraging PA, they included ways of overcoming barriers to promote PA in the intervention. They demonstrated that the groups, who received exercise treatment in addition to the behavioral intervention, had higher PAL following the intervention.…”
Section: Physical Activity Interventionsmentioning
confidence: 99%
“…Session attendance represented the number of GMCB sessions participants attended (ranging from 0 to 8). Interventionist satisfaction was rated on a 1 (not at all satisfied) to 10 (completely satisfied) scale.° As per Cohen's (1992) guidelines, effect sizes (d) were interpreted as small (d = 0.20), medium (d = 0.50), and large (d = 0.80). Effect size value is based on the transformed scores for LTPA and SRE and the raw score for action plans and physical outcome likelihood.…”
Section: Resultsmentioning
confidence: 99%
“…To address data non-normality, square-root transformations were applied to the LTPA and self-regulatory efficacy data prior to analyses. Cohen's d effect sizes were calculated with effects of 0.20, 0.50, and 0.80 indicating small, medium, and large effects, respectively (Cohen, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The education component was also based on prior theory-based, group-mediated cognitivebehavioural interventions in which education to increase self-efficacy, albeit in different domains of performance (i.e., self-efficacy to regulate barriers, to set goals, to schedule/plan exercise), has been shown to be effective in increasing exercise adherence. [43][44][45] The impact of the educational component included in the EE condition, which was designed to address the primary sources of self-efficacy (including mastery, social persuasion, and knowledge of physiological and affective states), may have been greater than that of the basic information typically included in fall-prevention educational sessions. As well, participants in this study presented with a mobility restriction and at least one other fall-risk factor; individuals with hip OA who also have lower levels of falls efficacy may present with a unique set of physical and social characteristics that increase their receptiveness to a combined programme of exercise and self-efficacy-enhancing education.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] The education component in the present study included three determinants of self-efficacy: enactive mastery experience, verbal persuasion, and physiological and affective states. 15 Mastery experience was developed by participants' learning strategies to prevent falls and consistently applying these strategies in day-to-day tasks.…”
Section: Eementioning
confidence: 99%